Three new species of the leafhopper genus Petalocephala from China (Hemiptera: Cicadellidae: Ledrinae) - Li, Rongrong; Zhang, Yalin; Cao, Yanghui (Zootaxa, 2026)
Three new species in the genus Petalocephala Stål, Petalocephala circumvoluta, P. rotunda and P. duplicata spp. nov. from China are described and illustrated. The sequences of the mitochondrial gene cytochrome c oxidase subunit 1 of the new species are provided.